The burden of hospitalization due to HPV infections in Tuscany, Central Italy. (December 2016) - Levi, M.; Bellini, I.; Sinisgalli, E.; Sala, A.; Indiani, L.; Bonanni, P.
Highlights: Hospitalization rates (HRs) for cervical cancers and genital warts in women have decreased. The cervical cancer screening programme, in place since 1999, has been successful. HRs in men have not being decreasing over a 13-year period of observation. The recommendation to extend the HPV vaccination programme to include boys is particularly welcome.